Corporate governance, credit risk, and financial literacy for Small Medium Enterprise in Indonesia - Mutamimah, Mutamimah; Tholib, Mochammad; Robiyanto, Robiyanto (Business: Theory and Practice, 2021)
The problem of SMEs in Indonesia as a “high-risk borrower” that has not been resolved until today. The purposes of this study was to analyze the financial literacy as mediating between corporate governance and SMEs’ credit risk in Indonesia. This sample method used purposive sampling: 1273 units of Trade and Service SMEs fostered by Central Java that received credit in 2018. Twenty percent of the totals were taken, so the total was 255 samples. The data collection technique used questionnaires and interviews. The number of questionnaires distributed were 255 with a response rate of 95%, so resulting 242 respondents. Data analysis used descriptive and Regression Method. The corporate governance shown by responsibility, independence, and fairness did not affect SMEs’ credit risk. In other words, transparency and accountability is effective in reducing SMEs’ credit risk. Also, financial literacy can strengthen the influence of transparency, accountability, and responsibility in reducing credit risk for SMEs in Indonesia.